Comparison Between Caudal and Combined Caudal with Spinal Anesthesia in Paediatric Bilateral Inguinal Hernia Surgery - Ali Hashmi, Syed Rafat; Ali Shah, Syed Qasim; Tariq, Waqas; Sarfaraz, Ahmed; Hassam bhalli, Hafiz Ahmed; Khan, Taimur Azam (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the analgesic efficacy and adverse effect profile of using caudal anaesthesia versus caudal combined with spinal anaesthesia for paediatric patients undergoing bilateral inguinal hernia surgery. Study Design: Prospective longitudinal study. Place and Duration of Study: Anaesthesia Department of Combined Military Hospital, Rawalpindi Pakistan, from Mar to Aug 2022. Methodology: Eighty paediatric patients between ages 5-10 years requiring bilateral inguinal hernia repair were included in the study. The Caudal Group received 0.25% Bupivacaine per the Armitage regime at a 1 ml/kg volume to reach an effective sensory level of T10. The Combined Group received spinal anaesthesia at a dose of 0.3 mg/kg for >15 kg patients and 0.4 mg/kg for 5-15 kg patients in the L4-L5 epidural space for an effective spinal level of T10. Once the spinal was administered, the same caudal dose as per the caudal Group’s Armitage regime. Results: The total duration of block and subsequent reversal to the S1 level was 326.2±12.6 minutes in the Caudal Group versus 441.22±31.8 minutes in the Combined Group (p<0.001). The mean time for the first dose of analgesia for pain was required after 5.27±0.24 hours in the caudal versus 7.03±0.20 hours in the Combined Group. Conclusion: We conclude that the combined caudal spinal approach offers better and superior pain control, resulting in less IV analgesic requirement and less hospital stay, offering a good alternative to general anaesthesia in paediatric surgeries.